The Influence of Parenting Style on Gadget Addiction Behavior among Adolescents - Mantika, Rania Kurnia (Acta Psychologia, 2026)
This study examines the influence of parenting style on gadget addiction behavior among children and adolescents in the context of increasing digital technology use. The rapid proliferation of gadgets has led to growing concerns about Gadget Addiction, which is associated with negative outcomes such as reduced social interaction, sleep disturbances, and declining academic performance. This research aims to analyze how different parenting styles affect the likelihood of developing gadget addiction and to identify which parenting approaches serve as risk or protective factors. The study adopts a quantitative approach using a survey method, with data collected through structured questionnaires measuring parenting styles based on the framework of Diana Baumrind and levels of gadget addiction behavior. The sample consists of adolescents selected through appropriate sampling techniques. Data are analyzed using regression analysis to determine the relationship between variables. The findings indicate that authoritative parenting has a significant negative effect on gadget addiction, while permissive, authoritarian, and neglectful parenting styles show positive associations with higher addiction levels. These results suggest that balanced supervision, emotional support, and clear communication are essential in preventing excessive gadget use. The study concludes that parenting style is a critical factor in shaping children’s digital behavior and highlights the need for effective parenting strategies and policy interventions to address the growing issue of gadget addiction.